2013
DOI: 10.1002/phar.1371
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study in Patients with Solid or Hematologic Malignancies of the Dose Proportionality of Subcutaneous Azacitidine and Its Pharmacokinetics in Patients with Severe Renal Impairment

Abstract: Azacitidine is dose proportional over the 25-100 mg/m2 dosing range. Overall, renal impairment had no important effect on azacitidine PK. Therefore, no initial azacitidine dose adjustment in patients with renal impairment is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…A phase I study conducted in patients with both solid and hematologic malignancies revealed that azacitidine is dose proportional over the 25-100 mg/m 2 dosing range, and renal impairment had no important effect on azacitidine pharmacokinetics. Therefore, initial dose adjustments at the start of therapy in patients with renal impairment are not required [Laille et al 2014]. Patients with hepatic dysfunction should have frequent monitoring of their liver function tests and blood counts as they may also experience a greater incidence of hematologic side-effects.…”
Section: Safetymentioning
confidence: 99%
“…A phase I study conducted in patients with both solid and hematologic malignancies revealed that azacitidine is dose proportional over the 25-100 mg/m 2 dosing range, and renal impairment had no important effect on azacitidine pharmacokinetics. Therefore, initial dose adjustments at the start of therapy in patients with renal impairment are not required [Laille et al 2014]. Patients with hepatic dysfunction should have frequent monitoring of their liver function tests and blood counts as they may also experience a greater incidence of hematologic side-effects.…”
Section: Safetymentioning
confidence: 99%
“…Early clinical and pharmacological data in humans and animals suggested that AZA, particularly when used intravenously, may be potentially nephrotoxic 23‐25 and the prescribing information of the drug recommends close monitoring of renal function during 5‐AZA administration. However, others and we have shown that AZA therapy is feasible in patients with all stages of CKD and pharmacokinetics of AZA are not affected significantly by renal impairment 26,27 . Adverse events, response rates and survival in patients with mild and moderate CKD were comparable with the ones with normal renal function and only severe CKD appears to be associated with higher toxicity 28 …”
Section: Discussionmentioning
confidence: 76%
“…In a study of patients with various tumor types who had renal impairment, azacitidine pharmacokinetics were unaffected (Laille et al, 2014). The SmPCs for both approved HMAs state that these drugs can be used in patients with renal impairment, and no specific modifications to the dose or frequency of administration are recommended (Dacogen SmPC; Vidaza SmPC).…”
Section: Special Populationsmentioning
confidence: 99%